The new humanities reader - Miller, Richard E. (Richard Earl) 1961- (Houghton Mifflin Company, 2003)
Designed to help students attain the analytical skills and big-picture overview necessary to become informed citizens, the collection contains challenging and important readings from diverse fields that address critical issues in contemporary society. Ideas and research from wide-ranging sources provide opportunities for students to synthesize materials and come up with their own ideas and solutions. Students will be engaged by reading and rereading, analyzing, and working with these selections because they present powerful ideas, not simply because they are models of good writing style.